Automated spectrometer interface for measurement of short half-life samples for neutron activation analysis - LAPOLLI, ANDRE L. (2018)
In this paper a source positioning system was developed, based on a HPGe detector coupled to a Canberra DAS 1000 data acquisition system and Canberra???s GENIE2K software and libraries. The system is composed of a step motor coupled to an Arduino Uno microcontroller, which is programmed using C language to allow for a source-detector distance between 0.3 and 20 cm - both components are coupled to a PC computer using the USB interface. In order to allow automated data acquisition, two additional pieces of software were developed. The first one, a Human-Machine Interface (HMI) programmed in Visual Basic 6, allows the programming and monitoring of the data acquisition process, and the other, in REXX language, controls the data acquisition process in the background. The HMI is user-friendly and versatile, so that the even rather complex data acquisition processes may be easily programmed. When the experiment scheme is saved, two files are created and used by the REXX code to control the acquisition process so that the data acquisition is automatically stopped and saved after a user-defined time, then the source is repositioned and data acquisition is cleared and restarted. While in the present stage the system only offers three distinct source positions, finer source-position adjusting is under development. In its present configuration the system has been tested for stability and repeatability in all three positions, with an excellent performance.